Components of the sympathetic nervous system as targets to modulate inflammation - rheumatoid arthritis synovial fibroblasts as neuron-like cells? - Xinkun Cheng; Torsten Lowin; Nadine Honke; Georg Pongratz (BMC, 2023)
Abstract Background Catecholamines are major neurotransmitters of the sympathetic nervous system (SNS) and they are of pivotal importance in regulating numerous physiological and pathological processes. Rheumatoid arthritis (RA) is influenced by the activity of the SNS and its neurotransmitters norepinephrine (NE) and dopamine (DA) and early sympathectomy alleviates experimental arthritis in mice. In contrast, late sympathectomy aggravates RA, since this procedure eliminates anti-inflammatory, tyrosine hydroxylase (TH) positive cells that appear in the course of RA. While it has been shown that B cells can take up, degrade and synthesize catecholamines it is still unclear whether this also applies to synovial fibroblasts, a mesenchymal cell that is actively engaged in propagating inflammation and cartilage destruction in RA. Therefore, this study aims to present a detailed description of the catecholamine pathway and its influence on human RA synovial fibroblasts (RASFs). Results RASFs express all catecholamine-related targets including the synthesizing enzymes TH, DOPA decarboxylase, dopamine beta-hydroxylase, and phenylethanolamine N-methyltransferase. Furthermore, vesicular monoamine transporters 1/2 (VMAT1/2), dopamine transporter (DAT) and norepinephrine transporter (NET) were detected. RASFs are also able to degrade catecholamines as they express monoaminoxidase A and B (MAO-A/MAO-B) and catechol-O-methyltransferase (COMT). TNF upregulated VMAT2, MAO-B and NET levels in RASFs. DA, NE and epinephrine (EPI) were produced by RASFs and extracellular levels were augmented by either MAO, COMT, VMAT or DAT/NET inhibition but also by tumor necrosis factor (TNF) stimulation. While exogenous DA decreased interleukin-6 (IL-6) production and cell viability at the highest concentration (100 μM), NE above 1 μM increased IL-6 levels with a concomitant decrease in cell viability. MAO-A and MAO-B inhibition had differential effects on unstimulated and TNF treated RASFs. The MAO-A inhibitor clorgyline fostered IL-6 production in unstimulated but not TNF stimulated RASFs (10 nM-1 μM) while reducing IL-6 at 100 μM with a dose-dependent decrease in cell viability in both groups. The MAO-B inhibitor lazabemide hydrochloride did only modestly decrease cell viability at 100 μM while enhancing IL-6 production in unstimulated RASFs and decreasing IL-6 in TNF stimulated cells. Conclusions RASFs possess a complete and functional catecholamine machinery whose function is altered under inflammatory conditions. Results from this study shed further light on the involvement of sympathetic neurotransmitters in RA pathology and might open therapeutic avenues to counteract inflammation with the MAO enzymes being key candidates.